The Small Open-Economy New Keynesian Phillips Curve: Empirical Evidence and Implied Inflation Dynamics - Alexander Mihailov; Fabio Rumler; Johann Scharler (Johannes Kepler University of Linz, Department of Economics, 2008)
This paper applies GMMestimation to assess empirically the small open-economy New Keynesian Phillips Curve derived in Galí and Monacelli (2005). We obtain a testable specification where fluctuations in the terms of trade enter explicitly, thus allowing a comparison of the relevance of domestic versus external determinants of CPI inflation dynamics. For most countries in our sample the expected relative change in the terms of trade emerges as a more relevant inflation driver than the contemporaneous domestic output gap. Overall, our results indicate some, albeit moderate, support for the tested relationship based on data from ten OECD countries typically classified as open economies.
Keywords: C32; C52; E31; F41; 330; New Keynesian Phillips Curve; small open economies; terms of trade fluctuations; inflation dynamics; GMM estimation; New-Keynesian Phillips Curve; Kleines-offenes-Land; Theorie; OECD-Staaten